HUMAN RIGHTS WATCH IN ADDRESSING SEXUAL VIOLENCE AGAINST WOMEN IN INDIA - Suwantra, Areline Putri; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This study aims to find out what efforts have been made by Human Rights Watch (HRW) and explain how efforts have been made by HRW to help victims of violence and sexual harassment in the workplace in India. The high number of sexual violence against women that occurs in India, especially in the workplace, has caused HRW as an international organization that focuses on cases of human rights violations to voice the conditions of sexual violence that occur in India.This research uses descriptive analysis method. Descriptive method is a method that tries to collect and organize data. The data collection technique used qualitative research based on secondary data taken from books, journals, official source websites. The author uses the perspective of feminism and the level of group analysis. The theory used in this study is the theory of the role of international organizations according to Clive Archer. The results of this study indicate that HRW's efforts in overcoming sexual violence against women in the workplace are by providing recommendations to the Indian government from the central government, regional to internal and local agencies, foreign/domestic companies, and countries in the world to enforce labor laws. so that there are no victims of sexual violence in the workplace.Keywords: HRW, sexual violence against women, workplace